2018
DOI: 10.1017/s104161021800039x
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for persons with dementia: what are they and how should they be studied?

Abstract: The publication of four papers concerning non-pharmacological interventions for persons with dementia heralds progress in the science of dementia care. The four papers are very diverse in focus and methodology, and include a study of the impact of a visual arts program on quality of life, communication, and well-being by Windle et al. (2017); an overview of systematic reviews of pharmacological and non-pharmacological interventions for the treatment of behavioral and psychological symptoms of dementia by Dyer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
(22 reference statements)
0
19
0
1
Order By: Relevance
“…Antipsychotics, which are commonly prescribed for behavioral and psychological symptoms of dementia (BPSD), are associated with serious adverse effects, including pneumonia, cardiovascular events, stroke, fractures, and kidney failure [7,8]. Above all, pharmacological interventions cannot fulfill the needs of PWD and their caregivers, including relief of pain and discomfort, the need for social contact, and alleviation of boredom [9]. For these reasons, a combination of pharmacological and nonpharmacological interventions (NPI) is strongly recommended for PWD [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotics, which are commonly prescribed for behavioral and psychological symptoms of dementia (BPSD), are associated with serious adverse effects, including pneumonia, cardiovascular events, stroke, fractures, and kidney failure [7,8]. Above all, pharmacological interventions cannot fulfill the needs of PWD and their caregivers, including relief of pain and discomfort, the need for social contact, and alleviation of boredom [9]. For these reasons, a combination of pharmacological and nonpharmacological interventions (NPI) is strongly recommended for PWD [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to include the voice of people with dementia, which in two recent reviews by Cole et al (2018) and Conway et al (2018) has been shown to be lacking in intervention and research design. People's needs for non-pharmacological, needs-addressing, and psychosocial interventions are likely to vary not only by type of dementia, as pointed out by Cohen-Mansfield (2018), but also by age. Considering perspective and age difference in the reception of messages might provoke a rethink of how campaigns are targeted, taking the position of the recipient more explicitly into account.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive interventions at the preclinical phases could be beneficial in delaying the onset of cognitive impairment [17][18][19]. Randomized control trials (RCTs) have offered some short-term impact of interventions that can improve cognitive function such as dance [20], exercise [21], physical activities [22], and psychological intervention [23].…”
Section: Introductionmentioning
confidence: 99%